Peran Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja ASN Di Walikota Jakarta Selatan Dimediasi Oleh Kompetensi - Yulinda Yulinda (Politeknik Kampar, 2023)
This study aims to examine and test the effect of work discipline, and work motivation mediated by competence on work performance at the Mayor of South Jakarta. Work discipline and work motivation as exogenous variables, competence as mediating variables and work performance as endogenous variables. This research was conducted on civil servants in the Mayor of South Jakarta. The background of this research is the development of human resources which aims to improve the quality of professionalism and the ability of employees to carry out their duties and functions optimally. Things that must be considered in the South Jakarta Mayor's agency such as work discipline, work motivation, competence and work performance. The sample in this study was taken using a purposive sampling method of 175 respondents. The analytical method used is the Structural Equation Model (SEM) and uses Partial Least Square (PLS) to test the strength of the direct and indirect relationship between various variables. The results of this study prove that work discipline affects work performance, motivation influences work performance, competence influences work performance, work discipline influences competence, work motivation influences competence, work discipline influences work performance through competence and work motivation influences performance work through competence.